Fads2 knockout mice reveal that ALA prevention of hepatic steatosis is dependent on delta-6 desaturase activity - Blair MacLeod; Chenxuan Wang; Liam H. Brown; Emma Borkowski; Manabu T. Nakamura; Kyle RD. Wells; Keith R. Brunt; Ewa Harasim-Symbor; Adrian Chabowski; David M. Mutch (Journal of Lipid Research, 2024)
The production of the omega-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) from alpha-linolenic acid (ALA) relies on the delta-6 desaturase (D6D) enzyme encoded by the Fads2 gene. While EPA and DHA reduce hepatic triacylglycerol (TAG) storage and regulate lipogenesis, the independent impact of ALA is less understood. To address this gap in knowledge, hepatic fatty acid metabolism was investigated in male wild-type (WT) and Fads2 knockout (KO) mice fed diets (16% kcal from fat) containing either lard (no n-3 LCPUFA), flaxseed oil (ALA-rich), or menhaden oil (EPA/DHA rich) for 21 weeks. Fat content and composition, as well as markers of lipogenesis, glyceroneogenesis, and TAG synthesis, were analyzed using histology, gas chromatography, and reverse transcription quantitative PCR (RT-qPCR). Mice fed the menhaden diet had significantly lower hepatic TAG compared to both lard- and flax-fed mice, concomitant with changes in n-3 and n-6 LCPUFA in both TAG and phospholipid (PL) fractions (all P < 0.05). Flax-fed WT mice had lower liver TAG content compared to their KO counterparts. Menhaden-fed mice had significantly lower expression of key lipogenic (Scd1, Srebp-1c, Fasn, Fads1, and Fads2), glyceroneogenic (Pck1), and TAG synthesis (Agpat3) genes compared to lard, with flax-fed mice showing some intermediate effects. Gene expression effects were independent of D6D activity, since no differences were detected between WT and KO mice fed the same diet. This study demonstrates that EPA/DHA and not ALA itself is critical for the prevention of hepatic steatosis.